1998
DOI: 10.1016/s0378-4266(97)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Investment opportunities and market reaction to capital expenditure decisions

Abstract: In this study, we argue that share price reaction to a ®rm's capital expenditure decisions depends critically on the market's assessment of the quality of its investment opportunities. We postulate that announcements of increases (decreases) in capital expenditures positively (negatively) a ect the stock prices of ®rms with valuable investment opportunities. Contrarily, we predict that announcements of increases (decreases) in capital spending negatively (positively) a ect the share prices of ®rms without such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 24 publications
12
92
0
5
Order By: Relevance
“…For instance, in the case of capital investments, Titman et al (2004) report a negative relation between the level of capital expenditures and stock returns, and interpret this result to be consistent with the overinvestment hypothesis. Chung et al (1998) report that increases in capital spending positively affect stock prices for firms with valuable investment opportunities. They, however, find the opposite result for firms without such opportunities.…”
Section: (Ii) Extent Of Investment In Randd Advertising and Capital Ementioning
confidence: 99%
“…For instance, in the case of capital investments, Titman et al (2004) report a negative relation between the level of capital expenditures and stock returns, and interpret this result to be consistent with the overinvestment hypothesis. Chung et al (1998) report that increases in capital spending positively affect stock prices for firms with valuable investment opportunities. They, however, find the opposite result for firms without such opportunities.…”
Section: (Ii) Extent Of Investment In Randd Advertising and Capital Ementioning
confidence: 99%
“…However, if the ratio is less than 1, an organisation may still have intellectual assets but are masked by liabilities (Abdolmohammadi, Greenlay, and Poole, 2001;Dzinkowski, 2000;Knight, 1999;Roos, Roos, Dragonetti, and Edvinsson, 1997, pp2;Sveiby, 1997, pp3-18). The second indicator was initially developed by the Nobel-prize winning economist James Tobin to predict the investment behavior affiliation (Chung, Wright, and Charoenwong, 1998;Flamholtz and Main, 1999). This method measures assets in traditional accounting by replacement cost.…”
Section: Liabilities and Measurement Indicatorsmentioning
confidence: 99%
“…The market reaction also varies with firm size, with large companies tending to experience smaller responses to announcements than do smaller firms. Chung et al (1998) reported that the quality of a company's investment opportunities is the primary determinant of market reactions to capital expenditure decisions. Our findings lend some support to a role for investment opportunities in market valuations.…”
Section: Introductionmentioning
confidence: 99%